Svømmetilbud målrettet etniske kvinder, Procesevaluering af en svømmeintervention - Andersen, Pernille Tangaard; Bak, Carsten Kronborg; Clausen, Camilla Tykgaard (Nordisk tidsskrift for helseforskning, 2014)
Evaluation of a swimming-intervention targeting female ethnical minorities. A health-promoting intervention in Korskærparken, established by the municipality of Fredericia, has been evaluated to identify potentials and barriers in health promotion targeting ethnic minorities. Factors that had a major effect in the success of the intervention were; a nearly cost free arrangement; the target groups ownership in the intervention; the fact that cultural and gender barriers were taken into account and the recruitment of participants through the local community, mentors and other participants. Barriers included dependence on economic support and practical arrangement.
Keywords: Health promotion; municipality; ethnic minorities. Helsefremme; kommune; etnisk minoritet.